Improving Local Economy Through Independent Enterprise Community (KUM); Rempung, Indonesia - Muh Hilmi Pauzi; Budi Setiawan; Azizul Ikwan (Sumber Belajar Sejahtera, 2023)
The research aimed to determine the role of community microeconomic programs in local enterprise community in Rempung with qualitative research approach. The finding shows that the implementation of microeconomic programs channelled through the program of local enterprise community reflected in three pillars. First, KUM activities function as a forum that provides capital loans to local communities. Second, the KUM program is a place of learning to get training and coaching in the developed business units. Third, KUM activities as a forum to develop business partnerships. The significant impact of the independent business group (KUM) program launched by the government can (a) create job opportunities for the community, (b) develop their potential and (c) foster an entrepreneurial spirit.